The role of epigenetic factors in childhood atopic dermatitis - E. P. Bystritskaia; N. N. Murashkin; E. A. Naumova; A. I. Materikin; V. K. Solntseva (Медицинская иммунология, 2024)
Atopic dermatitis (AD) is a genetically determined chronic inflammatory skin disease characterized by itching, relapsing course, age-related features of the lesion morphology and localization. The etiological factors contributing to the development of AD are: allergic reactions, inflammatory reactions in the skin, leading to a barrier disfunction, the affect and interaction of genetic and environmental factors. Epigenetic mechanisms also play a key role in immune regulation. The aim of this work is to study the genome-wide methylation profile in the skin of children with AD in the acute stage, as well as to determine changes in the expression level of immune response genes associated with common signaling pathways during therapy. Whole-genome sequencing was conducted to examine methylation in the skin samples from AD patients and controls. The stages of bioinformatics data processing were carried out. Changes in the expression levels of the TLR2, TLR9, IL4, IL13, CAMP, and DEFB1 genes before and after treatment were carried out using RT-PCR-RT on samples of mononuclear blood cells. When comparing samples from patients with AD and healthy children, changes were shown in the methylation of 2364 regions of genomic DNA with their corresponding specific genes. Among the identified genes, those related to processes associated with the pathogenesis of AD were selected. At the next stage, changes in the expression of the described immunity factors (TLR2, TLR9, IL-4, IL-13, DEFB1, CAMP) were assessed over time according to the type of treatment. For this purpose, patients were divided into 2 groups depending on the prescription of systemic therapy. Three months after treatment, the level of expression for all studied immune factors decreased. However, a significant decrease in expression for almost all parameters (except for the DEFB1 gene) was recorded in the group in which systemic therapy (dupilumab) was used in addition to topical treatment. At the same time, the SCORAD index after treatment improved by an average of 63% and amounted to 17±6.0 points. Thus, systemic therapy aimed at suppressing signaling of IL-4 and IL-13 cytokines indirectly leads to normalization of the expression levels of innate immune factors. Studying the regulation of molecular genetic mechanisms of immunity involved in the processes of inflammation in AD helps to clarify the immunopathogenesis of this disease, determine diagnostic markers and targets for drug therapy.